Analysis of Myth Barthes in SGM Milk Formula Advertisement “Aku Anak SGM Explore” Version - Rima Novia Ulfa; Rr. Astri Indriana Octavita; Tiarma Ika Yuliana (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
Advertisement is a medium of communication between producers and consumers. An advertisement can be done through various media such as newspapers, magazines, internet, radio and/or television. In advertisement, producers try to create a sign to make a hidden message (mitos) behind. Advertisement plays significant role in promoting such products because it spreads wider. Literacy of advertisements, through mass media is very essential in helping audiences to better see and understand how messages in the form of text, verbal and nonverbal are displayed through audio visual. The hidden message is created to convey consumers. So that, they can truly understand the message. Television is as one of the media to represent hidden message contained in an advertisement.This study aims to analyze how the signs contained in the texts displayed in the SGM formula advertisement, version